Essentials of medical terminology - Davies, Juanita J. (Thomson/Delmar Learning, 2008)
No prior exposure to medical terms? No problem! Designed for short medical terminology courses, this essentials-level learning resource uses simple language you can understand. Organized by body system, early chapters help you learn the foundation of medical word building with a basic analysis of medical terms, common anatomical roots, suffixes, and prefixes. Body system chapters present anatomy and physiology, terminology, common diseases, pronunciation, and abbreviations. Have fun while learning by taking quizzes, playing interactive games, and watching animations on the StudyWARE CD-ROM (Publisher description)